Liolaemus jamesi (Boulenger, 1891): restriction of the type locality and holotype characterization (Squamata: Liolaemidae) - Troncoso-Palacios, Jaime; de Gamboa, Margarita Ruiz; Campbell, Patrick D. (Zootaxa, 2019)
Liolaemus is one of the most diverse genus of lizards in the world (Esquerré et al. 2013), with 257 species listed in the last review focusing on its diversity (Abdala & Quinteros 2014). Certain species within this genus, especially the earlier ones, were described in very little detail, even lacking an appropriate description of the holotype and/or type locality. This has created uncertainties in the taxonomic identity of several Liolaemus species (Espinoza et al. 2011; Quinteros et al. 2008; Troncoso-Palacios & Garin 2013; Langstroth 2011).